New Variable Passive-Compliant Element Design for Quadruped Adaptation to Stiffness-Varying Terrain. (17th May 2016) - Koco, Edin; Mutka, Alan; Kovacic, Zdenko
This paper presents the design of a novel variable passive-compliant ( VPC ) element utilized as a lower-leg implant of a fully electrically driven quadruped robot. It is designed as a slider-piston mechanism which ensures that the force produced during a foot-ground contact is directly perpendicular to the contact surface of an actuated revolute spring. In this way, by altering the stiffness of quadruped legs in a closed-loop manner, the VPC element enables the quadruped robot to adapt to varying terrain characteristics, ensuring a constant hopping frequency over a wide range of terrain-stiffness variations. The designed VPC element and its beneficial characteristics are described in detail. Mathematical relations are formulated that help to describe the influence of the VPC element during vertical hopping of a quadruped robot. The properties of the quadruped research platform with integrated VPC element were verified in simulation and through experiments.